Singapore : Selected Issues. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2015)
External trade plays an important role in Singapore's economy, providing an important share of total value added. Singapore's exports have a relatively large import share; however, they also have a high level of complexity. As emphasized in previous studies, value-added in exports plays an important role in trade elasticities. The paper finds evidence that this is indeed the case for Singapore's export products. Products that have higher domestic value-added share also tend to have higher export price elasticity. Economic complexity is also related to export price elasticities: higher economic complexity is associated with lower price elasticity of exports. This relationship is stronger within certain product segments such as the machinery, mechanical appliances and computers as well as the pharmaceuticals segments. Trade elasticities are important to understand Singapore's exchange rate based monetary policy transmission. Exchange rate changes can affect profits and trade volumes differently, depending upon the price pass-through to import and export prices and the price elasticity of exports and imports. The import and export price pass-through can in return depend on trade elasticities. The paper also shows that there is important product heterogeneity with respect to trade elasticities; both across different product groups but also within individual product groups. This implies that structural changes in the product composition of trade can lead to sizeable changes in Singapore's trade elasticities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet